Islamic Religious Education as a Solution to Enhance Students' Social Awareness in Elementary School - Nurul Fadhlah; Nisdah Khairani Lubis; Nur Azizah Nst; Asrul Anwar; Rahmi Seri Hanida (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Social awareness is a fundamental dimension of student character development at the elementary school level, encompassing empathy, concern, responsibility, and cooperative social interaction. This study analyzes the role of Islamic Religious Education as a solution for enhancing the social awareness of students at SDN 154 Aek Ngali. A qualitative descriptive approach was employed, and data were collected through participatory observation, in-depth interviews, and documentation. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing and verification. The findings demonstrate that PAI is implemented contextually and practically, integrating social values into learning materials and methods. Forms of social awareness developed by students include empathy, mutual assistance, responsibility, cooperation, and discipline. Supporting factors include teacher role modeling, school support for religious habituation, and a conducive school environment, while inhibiting factors include limited learning time, differences in family backgrounds, and out-of-school environmental influences. Islamic Religious Education carries significant potential as a strategic solution for enhancing students' social awareness when implemented in an integrative, contextual, and sustained manner. This study is limited to a single public elementary school with a small number of informants, so its findings cannot be broadly generalized; future research is recommended to involve more schools with diverse socioeconomic and cultural backgrounds and to develop Islamic religious education learning models that systematically integrate social awareness indicators